The Existence of Traditional Rock Jumping (Fahombo) as a Cultural Heritage in Bawomataluo Village, South Nias Regency - Nofrizal, Dedi; Lubis, Hafiz Yazid; Gori, Enggellina; Telaumbanua, Nataniel (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2024)
This research aims to determine the appreciation of the people of Bawomataluo Village, South Nias Regency towards cultural values and the factors that contribute to the growth of the traditional sport of Stone Jumping (Fahombo). Documentation and preservation of traditional sports, Incorporating traditional sports into the curriculum to teach children about community culture. This research used qualitative descriptions, interviews, and observations. Data were analyzed using NVIVO 12 Plus. Data collection, FGDs, reduction, presentation, conclusion, and verification Ten participants participated in this study. Potential informants included stakeholders, community leaders, and sports activists. The results of this study are, 1) The number of people who know about stone jumping (Fahombo) shows that the community's efforts to preserve traditional sports are good. 2) Forming traditional sports coaching groups to promote the sport. 3) Traditional sporting events are widely promoted to local and migrant communities through traditional and digital media. 4) Preserving local culture by organizing annual events and festivals of the traditional sport of Stone Jumping (Fahombo), teaching it to the next generation, and recording it. 5) Tourism potential, organized traditional sports activities in Bawomataluo Village, South Nias, 6) Develop local tourism such as arts, traditional sports and improve resources.